New records of rare species in the Mediterranean Sea (December 2022) - FEDERICA MONTESANTO; MARCO ALBANO; DΕΝΙΖ AYAS; FEDERICO BETTI; GIOELE CAPILLO; MELIH ERTAN ÇINAR; MARIA CORSINI-FOKA; FABIO CROCETTA; ERTAN DAĞLI; CLAUDIO D’IGLIO; MARKOS DIGENIS; BRANKO DRAGIČEVIĆ; et al. (Mediterranean Marine Science, 2022)
This Collective Article presents information on 20 taxa belonging to five (5) Phyla: Cnidaria (2), Mollusca (8), Arthropoda (4), Echinodermata (1) and Chordata (5) recorded from the Alboran Sea to the Levantine Sea. These new records were found in seven (7) different ecoregions as follows: Alboran Sea: new record of the rare football octopus Ocythoe tuberculata in the harbour of Algeciras (Spain); Western Mediterranean Sea: first record of the isopod Arcturinella deltensis in the Ligurian Sea, and the third in the whole Mediterranean Sea; third Mediterranean site for the Muricidae Coralliophila ahuiri along the Italian coasts (Alghero); first and westernmost record of the goby Corcyrogobius liechtensteini from the Iberian Peninsula; new record of the sea slug Glaucus atlanticus from the coast of the Iberian Peninsula; first and easternmost record of Holothuria (Vaneyothuria) lentiginosa lentiginosa along the Italian coasts; Tunisian Plateau/Gulf of Sidra: seventh record of the oceanic squid Thysanoteuthis rhombus in Tunisia, and first for the Gulf of Gabes. Ionian Sea: second occurrence of the Atlantic tripletail Lobotes surinamensis in the Ionian Sea and first record from the Strait of Messina area; new record of the rare sea elephant Pterotrachea coronata from the Strait of Messina; Adriatic Sea: first record of a facies of football ascidian Diazona violacea in the South Adriatic Sea (Tremiti Island, Italy); two records of the sevengill shark Heptranchias perlo in Croatian waters after more than 70 years of absence of documented records in this area; first known occurrence of the nudibranch Jalonus hyalinus in Slovenian waters and also the first known occurrence of this species in the Adriatic Sea; first record of the nudibranch Okenia elegans in Slovenian waters; Aegean Sea: First record of the parasitic isopod Nerocila milesensis along Greek coasts (Crete island) as well as the second record worldwide; additional record of the brachyuran Paragalene longicrura collected from the Saronikos Gulf (Greece); first record of the siphonophore Rhizophysa filiformis in Greek waters as well as the second record of this species in the eastern Mediterranean basin; new record of the rare and protected angelshark Squatina aculeata along Turkish coasts; Levantine Sea: first record of the marine amphipod Caprella andreae in the Levantine Mediterranean shore of Israel, based on both morphological and molecular data; first occurrence of the cephalopod Tremoctopus violaceus along Turkish coasts, which confirms its presence in the north-eastern coasts of Turkey; record of a bloom of the thermophilic jellyfish Pelagia noctiluca in the north Levantine Sea.